Analisis Determinan Pendapatan Pedagang Kaki Lima Pecel Lele di Kota Samarinda dengan Peran Penjualan sebagai Variabel Intervening - Paramitha, Amelia; Gani, Irwan; Lestari, Diana (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This study aims to analyze the factors influencing the income of street vendors selling pecel lele in Samarinda City, with sales volume as an intervening variable. A quantitative approach was applied through a survey of 38 vendors, representing the total population. The variables analyzed include capital, labor, business duration, working hours, selling price, sales volume, and income. Path analysis results show that labor and business duration have a positive and significant effect on sales volume, while working hours have a negative effect. Capital and price do not significantly affect sales. Furthermore, sales volume significantly affects income. However, Sobel test results indicate that sales volume does not significantly mediate the relationship between independent variables and income. These findings suggest that income improvement is more effectively achieved by strengthening labor productivity and increasing business experience rather than relying solely on longer working hours or larger capital. This study contributes to the understanding of informal economic dynamics, particularly in micro-culinary enterprises, and provides a reference for policy formulation in micro-business development.